Deficiência do eixo ECA2/ANG-1-7/MAS altera respostas cardíacas e musculares promovidas pelo exercício voluntário em camundongos - Daisy Motta Santos (2013)
Physical training induces numerous physiological adaptations in the cardiovascular and skeletal muscle system related to changes in gene expression. These changes include modulation of the renin angiotensin system (RAS) components, especially the ACE2/Ang-(1-7)/MAS axis since its activation promotes similar effects to those of physical training. Thus, the aim of this study was to evaluate the effect of running wheel training in knockout mice for angiotensin-converting enzyme 2 (ACE2-KO) and angiotensin-(1-7) receptor (MAS-KO). For this we used C57Bl6 male mice (8-12 weeks old) WT, ACE2-KO and MAS- KO divided into voluntary exercise group or sedentary control (N = 4- 8 per group). The aerobic training lasted 6 weeks and the amount of exercise was measured by the number of rotations per day. The gene expression responses of factors related to physiological and pathological adaptations and RAS components in the left ventricle, skeletal muscle and adipose tissue were evaluated by real-time PCR (qPCR). Blood pressure was measured before and during the period of physical training using radio-telemetry. The plasma levels of angiotensin peptides were determined by mass spectrometry. The results showed that knockout of ACE2 gene decreases physical performance. In WT and MAS-KO mice aerobic training promotes cardiac hypertrophy but in MAS- KO it induced the expression of genes related to pathological conditions (ANP and BNP) and high plasmatic AngII / AngI ratio. The chronic aerobic exercise promoted an increase in skeletal muscle expression of FNDC5, irisin precursor, only in WT. In contrast, angiotensin-(1-7) receptor deficiency mice showed reduced FNDC5 expression in skeletal muscle (gastrocnemius and soleus) and no differences in inguinal adipose tissue UCP1 expression, opposite responses to that observed in WT mice. The MAS- KO group had elevated baseline blood pressure and paradoxal increase induced by physical training, while WT showed as expected, a reduction of blood pressure after 4 weeks of voluntary running. It was concluded that ACE2/Ang-(1-7)/MAS axis blocking alters cardiac and muscle skeletal changes promoted by the voluntary running.